2021
DOI: 10.3389/fnhum.2021.669902
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-Wide Association Study of Motor Coordination

Abstract: The ability to finely control our movement is key to achieving many of the educational milestones and life-skills we develop throughout our lives. Despite the centrality of coordination to early development, there is a vast gap in our understanding of the underlying biology. Like most complex traits, both genetics and environment influence motor coordination, however, the specific genes, early environmental risk factors and molecular pathways are unknown. Previous studies have shown that about 5% of school-age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…As post-hoc analyses, which were not pre-registered, we also used LDSC to test the genetic correlation between age at onset of walking and four other motor phenotypes; self-reported walking pace 103 , clinically ascertained muscle weakness in the pincer grip in elderly people 104 , motor coordination in childhood 105 and Parkinson’s Disease 106 .…”
Section: Methodsmentioning
confidence: 99%
“…As post-hoc analyses, which were not pre-registered, we also used LDSC to test the genetic correlation between age at onset of walking and four other motor phenotypes; self-reported walking pace 103 , clinically ascertained muscle weakness in the pincer grip in elderly people 104 , motor coordination in childhood 105 and Parkinson’s Disease 106 .…”
Section: Methodsmentioning
confidence: 99%
“…For each phenotype, we mapped QTLs using the fast linear regression equations of Haley and Knott. 86 The likelihood ratio statistic (LRS) was computed to assess the strength of genotype–phenotype associations. When appropriate, outlier values for specific traits were winsorized.…”
Section: Methodsmentioning
confidence: 99%
“…Our knowledge regarding these NDDs has mainly derived from comparative studies in human subjects, as research in animal models is limited and 2D/3D in vitro studies have not been conducted yet. Considering that molecular genetic testing coupled with genome-wide 10.3389/fnins.2022.1031075 association studies (GWAS) have identified causative genes in individuals with these NDDs (Niemi et al, 2018;Gialluisi et al, 2021;Mountford et al, 2021) it is of high importance to delve into the etiopathogenic mechanisms using both in vivo and in vitro research tools (Figures 1A,B).…”
Section: Other Neurodevelopmental Disordersmentioning
confidence: 99%